Co-creative Dynamics at the Defko Ak Niëp Lab: Prospects and Stakes - Mboa Nkoudou, Thomas Hervé (My University, 2021)
The maker movement refers to individual or collective do-it-yourself practices that make use of digital manufacturing in fields as varied as daily life, research, and industry. These practices are deployed in physical spaces called makerspaces. This generic term designates technological spaces of open innovation that are alternatively called fab labs, hubs, accelerators, incubators, hackerspaces, biohackerspaces, living labs, or coworking spaces. Makerspaces are generally equipped with digitally controlled machines, such as 3D printers or laser cutters, computer equipment, electronic kits, and a variety of other equipment or tools, like saws or sewing machines. Beyond the material aspect, makerspaces are characterized by their community dimension: regardless of their field, people with similar interests can come together to socialize, to collaborate, and to discuss common themes and problems. However, the maker movement—it is worth mentioning—is not a new phenomenon. As Michel Lallement says, “We have always been makers.”[1] This is all the more true in the African context, where resourcefulness, DIY, recycling, and repairing/mending practices are anchored in daily life. With an estimated over 100 makerspaces in Africa,[2] this ever-increasing expansion cannot go unnoticed
Keywords: Makerspaces; Africa; Digital imagineries; Commons